Comparison of the Efficiency of Solar PV Fixed, Single-Axis, and Dual-Axis Solar Trackers: A Review - Efendi, Mas; Mainil, Rahmat Imam; Aziz, Azridjal (Universitas Negeri Jakarta, 2025)
The global energy shortage, especially in developing countries, drives the search for alternative energy sources such as solar power, which is one of the cleanest energy sources. This research discusses the comparison of efficiency between solar PV fixed, single-axis solar trackers, and dual-axis solar trackers. The method used is a survey of the literature of multiple studies that only analyzes the efficiency of solar PV using different tracking devices. The efficiency data is normalized based on location factors and light intensity for a fair comparison. The results show that fixed solar panels are stationary and simple, serving as a baseline with 100 % efficiency. Single-axis panels track the sun horizontally, boosting efficiency by 25.6 % but with moderate complexity due to motors and controls. Dual-axis panels track the sun both horizontally and vertically, increasing efficiency by up to 50 % but with the highest complexity due to more moving parts and dual-axis control systems.